Implementasi Permainan Hijau-Hitam untuk Meningkatkan Minat Belajar Lari 100 Meter Siswa Kelas VII SMPN 11 Surabaya - Mochammad Hendra Saputra; Bambang Ferianto Tjahyo Kuntjoro; Ciciek Ismayadewi (Journal of Creative Student Research, 2024)
This study focuses on the low learning interest among seventh grade students at SMP Negeri 11 Surabaya. This study aims to collect information and investigate how the black-green game learning model improves students' learning interest. The design, implementation, observation, and reflection stages of the action research project were followed in this study. Thirty students from seventh grade of SMP Negeri 11 Surabaya participated in this study, which included pre-cycle, cycle 1, and cycle 2. Observation sheets, interviews, and documentation were used to collect data, which were then examined subjectively and using percentages. The results of this study indicate an increase in student learning outcomes based on data collected after cycles I and II, when game-based learning techniques were used.